Neoliberalism, Media and the Political - Phelan, S. author. aut Link
X, 242 p.
Keywords: Neoliberalism, Media and the Political examines the condition of media and journalism in neoliberal cultures. Emphasizing neoliberalism's status as a political ideology that is simultaneously hostile to politics, the book presents a critical theoretical argument supported by empirical illustrations from New Zealand, Ireland, the UK and the US.